1999
DOI: 10.1051/rnd:19990408
|View full text |Cite
|
Sign up to set email alerts
|

Effect of some phytoestrogens on metabolism of rat adipocytes

Abstract: (1 ltmol!L-') a été diminuée par la génistéine à sa plus forte concentration. La daidzéine (0,1 pmol.L-1 ) augmentait aussi la lipolyse. À sa plus forte concentration, la daidzéine a exercé un effet contraire similaire à celui de la génistéine. La zéaralénone diminuait la lipolyse, en particulier à forte concentration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
23
0
1

Year Published

2006
2006
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 14 publications
5
23
0
1
Order By: Relevance
“…Genistein has been shown to have potential anti-obesity effects, decreasing food intake, body weight and fat pad weight and inducing adipose tissue apoptosis in vivo [6,7] and inhibiting lipid accumulation and increasing lipolysis in vitro [8][9][10][11]. In this study, we examined the effect of genistein on differentiation, expression of adipocytespecific genes and expression of ERα and ERβ in primary human preadipocyte culture.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Genistein has been shown to have potential anti-obesity effects, decreasing food intake, body weight and fat pad weight and inducing adipose tissue apoptosis in vivo [6,7] and inhibiting lipid accumulation and increasing lipolysis in vitro [8][9][10][11]. In this study, we examined the effect of genistein on differentiation, expression of adipocytespecific genes and expression of ERα and ERβ in primary human preadipocyte culture.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown to decrease food intake, body weight and fat pad weight in ovariectomized female mice [6,7]. Genistein has been shown to inhibit lipid accumulation in 3T3-L1 cells [8][9][10] and also to inhibit cell proliferation and increase lipolysis in 3T3-L1 cells and rat adipocytes [8,11].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, some studies reported that genistein blocks adipogenesis and increases lipolysis in 3T3-L1 adipocytes (Harmon et al, 2002;Harmon and Harp, 2001;Hwang et al, 2005) and rat adipocytes (Kandulska et al, 1999;Szkudelska et al, 2000). Genistein produced a suppression effect on adipocyte differentiation by inhibiting the tyrosine phosphorylation of CCAAT/enhancer binding protein beta (C/EBPβ) (Harmon et al, 2002), inducing the expression of peroxisome proliterator-activated receptor alpha (PPARα) (Kim et al, 2004) and activating AMPactivated protein kinase (Hwang et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Genistein (G), 5 a soy isoflavone, was shown to decrease food intake, body weight, and fat pad weight in ovariectomized female mice (5,6). In adipocytes, G was shown to inhibit cell proliferation and increase lipolysis (7). In addition to estrogenic effects, G has effects on protein tyrosine kinases, apoptosis, cell proliferation, and angiogenesis (8)(9)(10) and can potentially affect adipose tissue through these mechanisms.…”
Section: Introductionmentioning
confidence: 99%